Horrid henry's sports: a horried factbook (packed with facts!) - Simon, Francesca; Ross, Tony (Orion Children's Books London, 2012)
"What is the world's most popular sport? Did you know that the Olympic gold medals are made mostly of silver? Did the Romans really do athletics in the nude? Weird and wonderful, hilarious and horrid, welcome to Horrid Henry's guide to everything you wanted to know about ... sports."--Back cover